Synergetically Selective Toluene Sensing in Hematite-Decorated Nickel Oxide Nanocorals - Suh, Jun Min; Shim, Young-Seok; Kim, Do Hong; Sohn, Woonbae; Jung, Youngmo; Lee, Seon Yong; Choi, Seokhoon; Kim, Yeon Hoo; Jeon, Jong-Myeong; Hong, Kootak; Kwon, Ki Chang; Park, Seo Yun; et al. (WILEY, 2017)
The decoration of p-type nickel oxide (NiO) with n-type hematite (alpha-Fe2O3) to achieve vertically ordered 1D nanostructures is an attractive strategy to enhance gas sensing properties. Herein, the authors report a facile method for alpha-Fe2O3 decoration of the whole surface of vertical NiO nanorods. An NiO/Fe heterostructure is deposited in multiple steps using a glancing angle deposition method, which is followed by the oxidation of Fe into alpha-Fe2O3. Thermally agglomerated alpha-Fe2O3 nanoparticles are uniformly distributed on the whole surface of the NiO nanorods. Due to the a-Fe2O3 decoration, the NiO nanorods exhibit a coral-like rough surface and, more interestingly, their preferential crystallographic orientation changed from ( 111) to ( 200). Compared to bare NiO nanorods, the alpha-Fe2O3-decorated NiO nanocorals exhibit a 45.4 times higher response to 50 ppm toluene ( C7H8) at 350 degrees C. Their theoretical detection limit for C7H8 is calculated to be approximate to 22 ppb. The observed unprecedented synergetic effects of alpha-Fe2O3- decorated NiO nanocorals for the extremely selective C7H8 sensing, as well as their facile synthetic route, establish a new perspective on heterostructured metal oxide 1D nanostructures for selective gas sensing.